Prosocial behavior predicts meaning in life during the COVID-19 pandemic: The longitudinal mediating role of perceived social support - He, Yumei; Liu, Qun; Turel, Ofir; He, Qinghua; Zhang, Shuyue (Frontiers in Public Health, 2023)
The COVID-19 pandemic was an unexpected, long-term negative event. Meaning in life has been linked to better psychological adjustment to such events. The current study uses longitudinal data collected during the COVID-19 pandemic to discover whether perceived social support mediates the relationship between six dimensions of prosocial behavior (Altruistic, Anonymous, Public, Compliant, Emotional, and Dire) and meaning in life. A sample of Chinese college students (N = 514) was tracked at three time points (T1, T2, and T3) during the COVID-19 outbreak. A cross-lagged panel model (CLPM) was used for mediation analysis. The mediation effect was found in all the dimensions of prosocial behavior except for Public prosocial behavior. We also found a longitudinal, bidirectional association between perceived social support and meaning in life. The current study contributes to the growing literature on the significance of prosocial behavior in predicting meaning in life.